2023
DOI: 10.3390/ma16072714
|View full text |Cite
|
Sign up to set email alerts
|

Multidimensional Study on the Wear of High-Speed, High-Temperature, Heavy-Load Bearings

Abstract: The friction and wear performance of high-performance bearings directly affects the accuracy and maneuverability of weapons and equipment. In this study, high-speed, high-temperature, and heavy-load durability experiments of weapon bearings were carried out, and their wear properties (i.e., surface wear, metamorphic layer, scanning electron microscopy/energy-dispersive spectroscopy (SEM/EDS), residual stress, and retained austenite) were analyzed in multiple dimensions. The results showed the following: (1) Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 34 publications
0
3
0
Order By: Relevance
“…The wear failure of bearings is a complex process involving several stages such as initial wear, stable wear, and severe wear [66]. The initial wear is related to the material properties of the bearings themselves, while the wear gradually slows down after entering the sTa wear stage [67,68]. In the later stages of wear, the bearing may undergo severe plastic deformation due to factors such as abrasive particles, changes in load, and other particles, which can accelerate the failure or damage of the bearing [69,70].…”
Section: (4) Generator Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The wear failure of bearings is a complex process involving several stages such as initial wear, stable wear, and severe wear [66]. The initial wear is related to the material properties of the bearings themselves, while the wear gradually slows down after entering the sTa wear stage [67,68]. In the later stages of wear, the bearing may undergo severe plastic deformation due to factors such as abrasive particles, changes in load, and other particles, which can accelerate the failure or damage of the bearing [69,70].…”
Section: (4) Generator Bearingsmentioning
confidence: 99%
“…The study found that taking into account reduced frictional interactions due to wear can lead to more accurate predictions of bearing wear. Wang et al [68] conducted multiple sets of high-speed, high-temperature, and heavy-duty durability experiments to investigate the frictional wear of high-performance bearings. They discovered that impurities adsorb onto the bearing surface after it has been damaged by abrasive wear.…”
Section: (4) Generator Bearingsmentioning
confidence: 99%
“…42CrMo steel is widely used in the manufacture of wind power bearing rings due to its unique wear resistance and high hardness 1 3 . However, at the same time, because the wind turbine bearing rings are in the harsh working environment in the field, under harsh working conditions such as cold, sand and tide, the surface is very prone to fatigue pitting 4 , wear 5 and even fracture 6 and other failure forms. This will adversely affect the normal operation of wind turbines bearing rings.…”
Section: Introductionmentioning
confidence: 99%